Noninvasive markers of inflammatory bowel disease activity - A. V. Nikitin; L. V. Vasilyeva; Anatoly A. Matiukhin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study noninvasive activity markers of inflammatory bowel diseases (IBD) and to estimate correlation between various diagnostic methods for an assessment of clinical and endoscopical activity of ulcerative colitis (UC) and Crohn's disease (CD). Material and methods. Original study included 67 patients with UC and CD in whom clinical and endoscopic activity of the disease with assessed by histological investigation of biopsy specimens. Blood serum cytokines: IL-4, IL-8, tumor necrosis factor α (TNF-α) and fecal calcium binding protein (calprotectin) were assessed. Results. Fecal calprotectin and TNF-α levels were much higher in patients with high disease activity and extent of inflammatory process. Spearman correlation coefficient between endoscopic features and fecal calprotectin (0,82) was higher in the UC patients, than between endoscopic parameters and TNF-α (0,78) in CD patients. Conclusions. Noninvasive inflammatory activity markers should be taken into account and decision-making on diagnostic and treatment strategy, as well as to decrease expensive and invasive diagnostic procedures.